2014
DOI: 10.1111/1346-8138.12439
|View full text |Cite
|
Sign up to set email alerts
|

Inverse correlation between microtubule‐associated protein 1A/1B‐light chain 3 and p62/sequestosome‐1 expression in the progression of cutaneous squamous cell carcinoma

Abstract: The expression of autophagy-related markers has occasionally been reported to correlate with the clinical stage of disease in patients with solid cancer, indicating autophagy activation. However, there have been no such reports for cutaneous squamous cell carcinoma. In this study, we investigated the expression levels of two autophagy-related markers, microtubule-associated protein IA/IB light chain 3 (LC3) and p62/sequestosome-1 (p62), in cutaneous squamous cell carcinoma specimens and assessed their correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 11 publications
3
14
0
1
Order By: Relevance
“…However, other investigations reported the protumoral activity of autophagy in skin cancer. In this line, an increased expression of the autophagy marker LC3 has been demonstrated in patients with SCC, which was associated with disease progression and prognosis of cancer [ 300 ]. Interestingly, an in vitro study showed that the inhibition of both Akt signaling and autophagy by the lysosomal inhibitor chloroquine enhanced the susceptibility of metastatic SCC cells to docetaxel-induced apoptosis [ 301 ].…”
Section: Inflammation and Skin Cancermentioning
confidence: 99%
“…However, other investigations reported the protumoral activity of autophagy in skin cancer. In this line, an increased expression of the autophagy marker LC3 has been demonstrated in patients with SCC, which was associated with disease progression and prognosis of cancer [ 300 ]. Interestingly, an in vitro study showed that the inhibition of both Akt signaling and autophagy by the lysosomal inhibitor chloroquine enhanced the susceptibility of metastatic SCC cells to docetaxel-induced apoptosis [ 301 ].…”
Section: Inflammation and Skin Cancermentioning
confidence: 99%
“…SQSTM1 is implicated in cancers of various organs, including kidney( Li et al , 2013 ), tuberous sclerosis complex ( Parkhitko et al , 2011 ), pancreatic ( Ling et al , 2012 ), prostate ( Chang et al , 2014 ), lung( Inoue et al , 2012 ), and oral ( Inui et al , 2013 ; Kuo et al , 2014 ). However, in cutaneous squamous cell carcinoma, SQSTM1 displays an inverse correlation with malignant progression ( Yoshihara et al , 2014 ), suggesting that SQSTM1 may have epidermis-specific functions. Similar to SQSTM1, NF-κB is known to stimulate inflammation and tumorigenesis in a wide range of tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that tumorigenesis, progression, invasion and metastasis of SCC involve several signal transduction pathways and molecules, including Notch, Integrin, tumor protein p53 (p53), epidermal growth factor receptor (EGFR) ( 5 ). Recently, researchers have demonstrated that autophagy might play a pivotal role in the pathogenesis of cSCC ( 6 , 7 ). Autophagy (term here used generally for macroautophagy) is a homeostatic mechanism under starvation or stressful conditions, resulting in the degradation of aggregated proteins and damaged organelles, and subsequently buffering metabolic stress by recycling intracellular components ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the relationship between autophagy and SCC pathogenesis and progression is complex. Previous studies have, however, indicated that autophagy-specific markers [high expression of Beclin 1 and/or microtubule-associated protein 1 light chain 3 (LC3), and lower level of p62/sequestosome-1] may serve a key role in controlling the tumorigenesis, progression and lymph-node metastasis of cSCC and may be prognostic predictors of clinical outcome ( 6 , 7 , 14 ).…”
Section: Introductionmentioning
confidence: 99%